2017
DOI: 10.1007/s00415-017-8503-2
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-associated neurocognitive disorder: epidemiology, pathogenesis, diagnosis, and treatment

Abstract: The modern antiretroviral treatment of human immunodeficiency virus (HIV-1) infection has considerably lowered the incidence of opportunistic infections. With the exception of the most severe dementia manifestations, the incidence and prevalence of HIV-associated neurocognitive disorders (HAND) have not decreased, and HAND continues to be relevant in daily clinical practice. Now, HAND occurs in earlier stages of HIV infection, and the clinical course differs from that before the widespread use of combination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
200
1
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(226 citation statements)
references
References 129 publications
(160 reference statements)
2
200
1
13
Order By: Relevance
“…Studies have shown that different brain regions that interact to promote cognitive functions show less-coordinated activation with aging, suggesting a vast loss of integrative function, related in part, to disruption of neuronal connections in different cortical regions [15,16]. There was a very high percentage of drug users in our cohort.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have shown that different brain regions that interact to promote cognitive functions show less-coordinated activation with aging, suggesting a vast loss of integrative function, related in part, to disruption of neuronal connections in different cortical regions [15,16]. There was a very high percentage of drug users in our cohort.…”
Section: Discussionmentioning
confidence: 84%
“…Reports have demonstrated that high viral burden and abnormal pathology are present within this brain region. 65,66 Herein, we decided to infect animals for a longer period of time (12 days) to more closely mimic the chronic nature of the disease. We investigated the same markers as the in vitro work and a significant increase in the inflammatory markers: TNFα, IL-1β, IFNγ, CCL2, CCL3, and C3 was evident after 12 days of infection ( Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“… may be explained by the different CDT interpretation model and gold standard battery we used. The observed poor performance may also be attributable to cortical imprinting , which makes CDT less effective in revealing subcortical deficits, which are still more common in HAND patients .…”
Section: Discussionmentioning
confidence: 99%
“…The discordance between our results and those reported by Levy et al [22] may be explained by the different CDT interpretation model and gold standard battery we used. The observed poor performance may also be attributable to cortical imprinting [34], which makes CDT less effective in revealing subcortical deficits, which are still more common in HAND patients [35,36]. 3QT, which is based on symptom reporting, has been proposed as an easy-to-use screening tool for HAND by Simioni et al [11].…”
Section: Discussionmentioning
confidence: 99%